Use of an Architectural Design Approach in The Development of the Manuscript of Bed of Sloth - Moore, Dave (Auckland University of Technology, 2016)
This submission is a thesis in two parts. The first is the third full draft of a creative work in Social Realist (SR) novel form entitled Bed of Sloth developed during the Master of Creative Writing (MCW) programme 2016. In the story two friends, formerly lovers, maintain their relationship over a 35 year period, from opposite ends of the earth and with an ultimate plan to meet up for a major trip together. It is set in the UK, France, the Netherlands and Australia. Antagonistic forces acting against them over these years are multiple, including: Class, sometimes justifiably suspicious partners and the impact of The Troubles on their respective families. In the second part, the exegetical work reports on the research process regarding content and writing methods. Use of an architectural-style three stage model of development for the latter is described and explored. Personal motivations for writing Bed of Sloth, key themes and the historical context of the period are then discussed with reference to the relevant SR literature and other creative forms. The exegesis concludes with thoughts on the future for Bed of Sloth beyond the MCW programme; and suggests that processes with more collaborative final stages may in this case have merit.
Keywords: Social realism; Exegesis; Architectural design approach; Contemporary; Friendships